An exploration of LMS adoption in employee training in Iceland - Magnús Olsen Guðmundsson 1981- (2023)
Organizations are using electronic learning (eLearning) solutions more frequently for employee training and development as technology continues to transform the workplace. The reasons behind its acceptance, particularly in the context of Iceland, are yet unstudied. By analyzing the drivers, advantages, and difficulties related to the use of eLearning through Learning Management Systems (LMS) in Icelandic businesses, this thesis aims to bridge this gap. This study explains the dynamics of eLearning acceptance in employee training programs using quantitative and qualitative data collected from an online poll of random employees and semi-structured interviews with five Human Resource Management (HRM) practitioners. It explores the background of employee training in Iceland, the benefits, and drawbacks of integrating eLearning, and the crucial factors that affect its use, such as organizational culture and employee attitudes. By considering several factors like technology's contribution, cost-efficiency, and ease of accessibility, the study offers insights into the effectiveness of eLearning as a training approach. It also gives suggestions for Icelandic businesses looking to successfully incorporate eLearning into their employee training programs. Overall, this study adds to the body of knowledge on the use of eLearning in employee training programs and has consequences for organizations on a practical level. This study's results highlight eLearning's potential to improve organizational outcomes and employee performance in Iceland and encourage additional investigation in this developing area. Keywords: Employee training and development, eLearning, Learning management system, Electronic human resource management Abbreviations: E-HRM = Electronic human resource management, eLearning = electronic human resource management, HRM = Human resource management, Learning management system = LMS, T&D = Training and development